2021
DOI: 10.2147/nss.s335288
|View full text |Cite
|
Sign up to set email alerts
|

Association of Hypertriglyceridemic Waist Phenotype with Obstructive Sleep Apnea: A Cross-Sectional Study

Abstract: Objective Hypertriglyceridemic waist (HTGW) phenotype is an independent risk factor for metabolic disorders. Although obstructive sleep apnea (OSA) is associated with metabolic disorders, it is unclear whether there is an association between HTGW phenotype and OSA. Methods We enrolled consecutive participants presenting to a sleep center in Shanghai, China. Full-night polysomnography was performed, and serum triglyceride (TG) levels and waist circumference (WC) were cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Wrzosek et al reported that significant correlations were found between the PSQI scores and serum triglycerides [ 36 ]. Compared with normal sleep time, insomnia in patients with sleep disorders was often accompanied by an increase in serum triglycerides [ 37 ]. Insomnia was related to most cases of cardiovascular and cerebrovascular diseases, some of which may be partially mediated by high triglycerides [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wrzosek et al reported that significant correlations were found between the PSQI scores and serum triglycerides [ 36 ]. Compared with normal sleep time, insomnia in patients with sleep disorders was often accompanied by an increase in serum triglycerides [ 37 ]. Insomnia was related to most cases of cardiovascular and cerebrovascular diseases, some of which may be partially mediated by high triglycerides [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Possible answers for all three questions were never, rarely (1‐2 times per week), occasionally (3‐4 times per week), or frequently (≥5 times per week). Individuals who answered “occasionally” or “frequently” to all three questions were determined to be positive for “obstructive sleep apnea symptoms” in our analysis as in prior literature 26 . Data on OSA symptoms was available in a subset of the cohort (NHANES 2005‐2006, 2016‐2017, 2017‐2018, n = 4651).…”
Section: Methodsmentioning
confidence: 99%